Does the IFRS 16 affect the key ratios of listed companies? Evidence from Poland - Anna Białek-Jaworska; Justyna Dobroszek; Paulina Szatkowska (International Journal of Management and Economics, 2022)
The paper aims to assess the International Financial Reporting Standard (IFRS) 16 "Leases" impact on the lessees' financial situation. The study was conducted on the financial data for 2018-2019 of 494 companies listed on the Warsaw Stock Exchange using the difference-in-differences (DID) method. The hand-collected data on lease usage retrieved from the financial statements and the data for financial ratios obtained from the Orbis database were used. The research sample includes 308 preparers under IFRS and 186 entities applying accounting policies under the Polish Accounting Act. It is shown that the IFRS 16 implementation resulted in a significant increase in the debt-to-equity and debt-to-total assets ratios of lessees and a decrease in the profitability. We identified significant leverage increase in the trade and services sectors. The results confirm the conclusions of previous studies based on estimates, whose authors expected a significant differential effect of IFRS 16 implementation between industries.
Keywords: M40; M41; M48; 650; difference in differences; leverage; profitability; leasing